The art of landscape lighting a designer's companion - Moyer, Janet Lennox, author
Following on from the critically acclaimed The Landscape Lighting Book, this is the lighting design companion every professional and student in landscape architecture needs. Written by an award-winning internationally renowned landscape designer, with over 40 years' experience in professional practice, The Art of Landscape Lighting takes the reader step-by-step through Janet Lennox Moyer's design process. Personal and accessible in tone, the book covers tools, equipment, techniques, effects, installation, design composition and challenges using built case studies spanning the author's career. Each project takes you through the process of how to plan compositions; selecting what should be lit and what should remain unlit; how to prioritise the importance of multiple elements; balancing brightness relationships; providing visual transportation across scenes; lighting the same space in different ways and, importantly, guidance on when designs are complete. Lavishly designed and illustrated with over 800 full colour photographs, showcasing projects from start to finish, it additionally includes new landscape lighting equipment and techniques developed by Moyer throughout her career. This includes shorescraping, rainwall lighting, approaches for lighting water features and sculptures, and the 3-prong stake. Aimed at practicing professionals and students in landscape architecture, this book is the must-have inspirational resource that provides you with everything you need to design and implement landscape lighting across multiple scales"-Provided by publisher.